Incentivising ‘Regenerative Value’ to Improve Sustainability Outcomes (2022)
ABSTRACT: Chapter 5 studies how regenerative value can foster positive actions towards climate change and stresses the importance of collaborative structures for nurturing transitions. This chapter argues that whilst specific policy instruments, industry standards, and the Sustainable Development Goals (SDGS) have an important role to play in establishing climate targets, incentivising action and monitoring outcomes requires a more interdependent approach to drive green initiatives at all scales.